Secret Law: The Politics of Appointments to the U.S. Foreign Intelligence Surveillance Court. (2nd July 2016) - Seabrook, Nicholas R.; Cole, Nicholas C.
ABSTRACT: This study investigates the politics of appointments to the United States Foreign Intelligence Surveillance Court, the court established under the 1978 Foreign Intelligence Surveillance Act (FISA) to review secret federal government requests for warrants related to national security investigations. Since the FISA Court's creation, its members have been appointed entirely at the discretion of the Chief Justice of the United States, who selects FISA Court judges from among the pool of existing U.S. District Court judges. Using data on the common space scores of the federal district judges appointed to the court, and the limited information available on the court's decisions, we explore the implications of this, both for the ideological makeup of the FISA Court's judges and for the oversight function they perform. The results suggest that the court has become decidedly more conservative in recent years, far more so than the district courts overall, with potentially serious implications for its ability to function as an effective check on the power of the executive branch.